Berberine and rifaximin effects on small intestinal bacterial overgrowth: Study protocol for an investigator-initiated, double-arm, open-label, randomized clinical trial (BRIEF-SIBO study) - Guo, Huaizhu; Lu, Siqi; Zhang, Jindong; Chen, Chen; Du, Yanlin; Wang, Kun; Duan, Liping (Frontiers in Pharmacology, 2023)
Introduction: Small intestinal bacterial overgrowth (SIBO) leads to non-specific abdominal discomfort and nutrient malabsorption. Currently, rifaximin is widely applied in SIBO based on its antibacterial and non-absorbable nature. Berberine is a natural component of many popular medicine plants that ameliorates intestinal inflammation in humans through its modification of the gut microbiota. Potential effect of berberine to the gut may provide therapeutic target for SIBO. We aimed to evaluate the effect of berberine compared with rifaximin on SIBO patients. Methods: This is an investigator-initiated, single-center, open-label, double-arm randomized controlled trial, termed BRIEF-SIBO (Berberine and rifaximin effects for small intestinal bacterial overgrowth). In total, 180 patients will be recruited and allocated to an intervention group (berberine) and a control group (rifaximin). Each participant will receive one 400 mg drug twice a day (800 mg daily) for 2 weeks. The total follow-up period is 6 weeks from the start of medication. The primary outcome is a negative breath test. The secondary outcomes include abdominal symptom relief and alteration in gut microbiota. Efficacy assessment will be performed every 2 weeks, as well as safety assessment during the treatment. The primary hypothesis is that berberine is not inferior to rifaximin for SIBO. Discussion: The BRIEF-SIBO study is the first clinical trial assessing the eradication effects of 2 weeks of berberine treatment in SIBO patients. The effect of berberine will be fully verified by using rifaximin as the positive control. The findings of this study may have implications for the management of SIBO, especially increasing the awareness of both physicians and patients who are suffering from long-term abdominal discomfort and avoiding excessive examination.